Artificial Intelligence in Precision Medicine: Enhancing Chronic Disease Management and Genomic Drug Discovery through Predictive Modeling - Roy, Antu; Ashik, Md.; Khan, Nirupam; Karim, Delwar; Kumar, Amit (The Eastasouth Journal of Information System and Computer Science, 2025)
This paper explores the transformative role of Explainable Artificial Intelligence (XAI) in precision medicine, focusing on its application in chronic disease management and genomic drug discovery. Through two detailed workflow diagrams, the study highlights the integration of XAI within the clinical decision-making pipeline and biomedical research domains. Figure 1 illustrates a comprehensive process encompassing data acquisition, preprocessing, predictive modeling, and clinician feedback, all underpinned by XAI techniques such as SHAP, LIME, and attention mechanisms. This workflow enhances trust and transparency in AI-driven predictions, empowering clinicians to interpret and act on machine-generated insights. Figure 2 extends this understanding by mapping XAI applications to chronic disease monitoring and genomic analysis. In chronic care, XAI enables risk stratification and personalized interventions, while in genomic drug discovery, it facilitates the identification of potential targets through interpretable machine learning models. Together, these figures underscore XAI’s critical role in translating complex data into actionable healthcare outcomes. By promoting accountability, user trust, and informed decision-making, XAI emerges as a cornerstone for the ethical and effective deployment of artificial intelligence in precision medicine. The paper concludes that integrating explainability into AI models is not only a technical necessity but also a fundamental step toward safer, smarter, and more inclusive healthcare systems.